2013
DOI: 10.1182/blood-2013-08-519124
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the factor VIII C2 domain in a ternary complex with 2 inhibitor antibodies reveals classical and nonclassical epitopes

Abstract: Key Points Antibodies against the factor VIII C2 domain inhibit procoagulant function. Crystal structure analysis of a C2 domain/antibody ternary complex describes epitopes for classical and nonclassical inhibitory antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 61 publications
9
41
1
Order By: Relevance
“…32 Similarly, we expect that the B-cell epitope residues identified herein comprise a subset of the actual contact areas between each inhibitory antibody and FVIII. This expectation has been confirmed, in part, by recent crystallographic studies illustrating the epitope recognized by another type BC inhibitor (mAb G99) 33,34 and by a nuclear magnetic resonance/mass spectrometry study that identified several FVIII-C2 surfaces occluded by the binding of 4 neutralizing mAbs. 35 SPR-based assignments of epitope residues presented herein are consistent with the regions identified using the same or similar mAbs and these other techniques.…”
Section: Blood 24 April 2014 X Volume 123 Number 17 B-cell Epitopessupporting
confidence: 52%
See 1 more Smart Citation
“…32 Similarly, we expect that the B-cell epitope residues identified herein comprise a subset of the actual contact areas between each inhibitory antibody and FVIII. This expectation has been confirmed, in part, by recent crystallographic studies illustrating the epitope recognized by another type BC inhibitor (mAb G99) 33,34 and by a nuclear magnetic resonance/mass spectrometry study that identified several FVIII-C2 surfaces occluded by the binding of 4 neutralizing mAbs. 35 SPR-based assignments of epitope residues presented herein are consistent with the regions identified using the same or similar mAbs and these other techniques.…”
Section: Blood 24 April 2014 X Volume 123 Number 17 B-cell Epitopessupporting
confidence: 52%
“…This expectation has been confirmed, in part, by recent crystallographic studies illustrating the epitope recognized by another type BC inhibitor (mAb G99) 33,34 and by a nuclear magnetic resonance/mass spectrometry study that identified several FVIII-C2 surfaces occluded by the binding of 4 neutralizing mAbs.…”
supporting
confidence: 52%
“…Epitopes, mechanisms of action and kinetics have been defined for a large collection of anti‐A2 and C2 domain murine monoclonal antibodies (MAbs) demonstrating that the murine hemophilia A model recapitulates many features of the anti‐FVIII immune response observed in humans . Recently, high‐resolution structural data of anti‐hFVIII MAbs in complex with the FVIII C2 domain using small angle X‐ray scattering, X‐ray crystallography, and hydrogen‐deuterium exchange mass spectrometry were obtained and have brought the understanding of inhibitor mechanism of action to the atomic level .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Healey et al 11 demonstrated a predominance of anti-fVIII antibodies to the A2 and C2 domains of fVIII in a murine hemophilia A model, but antibodies to the other domains were also detected. Characterization of the structural and functional properties of anti-A2 and anti-C2 domain monoclonal antibodies (mAbs) has advanced our understanding of the epitope spectrum of anti-fVIII antibodies [12][13][14][15] and their mechanisms of inhibition. [16][17][18][19] However, there is increasing evidence of the C1 domain's contribution to fVIII function and immunogenicity.…”
Section: Introductionmentioning
confidence: 99%